The Defiance of Postproverbials in 9ice and Asa’s Petepete (2022)
Proverbs are the origin of postproverbial, albeit there is a purposeful misinterpretation of their meaning as time goes on and humour develops. The Yoruba communication system relies heavily on proverbs, which are an integral aspect of postproverbial meanings. When it is culturally appropriate, proverbs are frequently employed by adults, while younger people are expected to speak modestly and refrain from using proverbs when speaking with seniors. The created postproverbials, which are well-liked and employed by people of all ages and are utilised without any set rules, are used as "catchphrases" to lampoon events or establish meaning in circumstances, particularly among individuals who have a common experience. The postproverbials in Petepete lyrics, are examined in relation to the neo-Yoruba experience. Purposive random sampling is engaged in the selection of the lyrics being part of the qualitative research approach employed. The proverbs in Petepete are employed as prefixes to their postproverbial forms, causing the original proverbs to be remixed in communication systems, in language use and new media such as in memes and gifs. The deviation agreement in the Yoruba communication system's postproverbial comprehension is the concern of this paper.